Effect of calcination temperature on bilayer TiO2/ZnO and ZnO/TiO2 thin films - Zulkiflee, Nur Syahraain (2018)
Thin film is a thin material that resulting from the condensation of species through the deposition of atoms on substrate. Thin films are usually used in the production of electronic devices, optical coatings, solar cells, and for decorative items. The result of thin film from titanium dioxide (TiO2) and zinc oxide (ZnO) have good photocatalytic properties, high refractive index, a high dielectric constant, and good thermal stability. In this study, bilayer TiO2/ZnO and ZnO/TiO2 thin films were produced using sol-gel synthesis with titanium (IV) butoxide as the precursor for TiO2, while zinc acetate dehydrate as precursor material for ZnO. Thin films are produced on glass substrate via spin coating method at speed of 3000 rpm and were calcined at different calcination temperatures that are 400 oC, 500 oC, and 600 oC. The X-ray diffraction (XRD) technique revealed that hisghest anatase crystalline phase for TiO2 growth with orientation (1 0 1), while the ZnO crystal phase, zincite occurred at the highest intensity with (1 0 1) orientation. Thin film morphology analysis through field emission scanning electron microscope (FESEM) has shown that particle distribution of thin film is more uniform when the temperature increased. Based on the characterization and analysis of the atomic force microscope (AFM), the root-mean-square (RMS) value for TiO2/ZnO and ZnO/TiO2 decreases as the calcination temperature increase. Meanwhile, the transmittance spectra increase when the calcination temperature increases. With further increase in temperature, the band gap energy were about 3.21 eV to 3.36 eV for TiO₂/ZnO thin films and 3.26 eV to 3.74 eV for ZnO/TiO₂ thin films. The bilayer TiO2/ZnO thin film had the highest reaction rate, K which is 0.0972 h-1 for photocatalytic activity. The characteristics of bilayer TiO2/ZnO and ZnO/TiO2 thin-film is strongly influenced by the calcination temperature and the presence and combination between the two types of materials.